Research returns redux: a meta-analysis of the returns to agricultural R&D - Alston, Julian M.; Marra, Michele C.; Pardey, Philip G.; Wyatt, T. J. (Wiley, 2000)
A total of 289 studies of returns to agricultural R&D were compiled and these provide 1821 estimates of rates of return. After removing statistical outliers and incomplete observations, across the remaining 1128 observations the estimated annual rates of return averaged 65 per cent overall — 80 per cent for research only, 80 per cent for extension only, and 47 per cent for research and extension combined. These averages reveal little meaningful information from a large body of literature, which provides rate‐of‐return estimates that are often not directly comparable. This study was aimed at trying to account for the differences. Several features of the methods used by research evaluators matter, in particular assumptions about lag lengths and the nature of the research‐induced supply shift.